Electronic and Mechanical Coupling in Bent ZnO Nanowires - Han, Xiaobing; Kou, Liangzhi; Lang, Xiaoli; Xia, Jianbai; Wang, Ning; Qin, Rui; Lu, Jing; Xu, Jun; Liao, Zhimin; Zhang, Xinzheng; Shan, Xudong; Song, Xuefeng; et al. (Advanced materials (Weinheim), 2009)
A red shift of the exciton of ZnO nanowires is efficiently produced by bending strain, as demonstrated by a low‐temperature (81 K) cathodoluminescence (CL) study of ZnO nanowires bent into L‐ or S‐shapes. The figure shows a nanowire (Fig. a) with the positions of CL measurements marked. The corresponding CL spectra—revealing a peak shift and broadening in the region of the bend—are shown in Figure b.